Habit or lack of education? Hypohydration is present in elite senior judo athletes even during a weight-stable training camp - Ceylan, B.; Tascan, M. B.; Simenko, J.; Balci, S. S. (International Journal of Sports Science & Coaching, 2023)
It has been well-documented that high-level judo athletes presented a high level of hypohydration during weight-cutting and competition periods. However, there is a lack of studies investigating the hydration status of high-level judo athletes during a weight-stable training period. Therefore, this study aimed to investigate elite judo athletes` hydration status, body mass change, and fluid intake during a weight-stable training camp. Twenty-seven judo athletes (women n = 8, men n = 19, body weight = 79.6 ± 20.9 kg) from the senior national judo team voluntarily participated in this study. Data were collected in the morning after waking up and before and after the morning and evening training sessions. On the second day, the measurements were taken again in the morning after waking up. Urine-specific gravity (USG) was classified as hydrated (USG < 1.020) and hypohydrated (USG = 1.020). The athletes` USG values measured on two consecutive mornings increased (1.025 ± 0.007 to 1.029 ± 0.006) during 24 h, in which athletes performed judo training in the morning and evening. Moreover, sex and weight category did not affect the changes in USG values (p > .05). Most of the elite judo athletes presented hypohydration (92.6%). The relationship between the fluid intake of the athletes and the changes in USG and body weight values during 24 h was not significant (p > .05). The current study`s findings revealed that high-level judo athletes present a high level of hypohydration even during a weight-stable training camp. Furthermore, the training sessions during the experiment period (24 h) worsened the hydration status of the senior athletes in all weight categories for both women and men.